2016
DOI: 10.3310/pgfar04170
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of patients’ experiences as a resource for choice and decision-making in health care: a creative, interdisciplinary mixed-method study in digital health

Abstract: BackgroundTraditional health information has been based on facts and figures and not on patient experience (PEx). Websites featuring people’s accounts of their experiences of health and illness are popular as a source of information, support and much else. However, there are concerns that experiential information on the internet might have adverse effects on health.AimsTo find out whether, when and how the NHS should incorporate PEx into online health information and elucidate the mechanisms through which PEx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 155 publications
0
21
0
Order By: Relevance
“…The study formed part of a larger programme of work investigating the value of online patient experiences 33. We conducted a phase II pilot randomised single-blind trial with the aim of assessing the feasibility and impact of patient-experience (PEx)-based websites compared with matched health information websites that did not contain experiential information.…”
Section: Methodsmentioning
confidence: 99%
“…The study formed part of a larger programme of work investigating the value of online patient experiences 33. We conducted a phase II pilot randomised single-blind trial with the aim of assessing the feasibility and impact of patient-experience (PEx)-based websites compared with matched health information websites that did not contain experiential information.…”
Section: Methodsmentioning
confidence: 99%
“…For example, to share with other potential service users. Ziebland et al (2016) reviewed the literature and identified that hearing about other people's experiences of a health condition could influence a person's own health through seven domains: finding information, feeling supported, maintaining relationships, using health services, changing behaviours, learning to tell the story and visualising illness. Study E found that some people see giving feedback as a form of public accountability for the service and part of a sense of 'caring for care' (although it is not always used as such by the healthcare providers).…”
Section: For Sharing With Other Patients and Publicmentioning
confidence: 99%
“…37 Existing online resources to aid women's help seeking tend to rely on individuals' accounts of their own experiences. 44 While these can provide contextual information about causes and consequences and help people to understand what may happen, 45 they can exclude others if the experiences presented are not shared. 46 To foster inclusivity, we chose to present a generic meta-narrative rather than a series T A B L E 5 Interim feedback on the involvement process…”
Section: Utilitymentioning
confidence: 99%